Chemical profile and inhibition of MDR bacteria by the essential oil of Laurus nobilis L. and its major compound 1, 8-cineol. (September 2021) - Saraiva, Cícero Roberto Nascimento; de Fatima Alves Nonato, Carla; Camilo, Cicera Janaine; de Araújo, Ana Carolina Justino; Rodrigues, Fabiola Fernandes Galvão; Coutinho, Henrique Douglas Melo; da Costa, José Galberto Martins
Abstract: Laurus nobilis L. (Lauraceae), which is popularly known as laurel. This species is commonly employed in the food, cosmetic and pharmaceutical industries. The objective of this study was to evaluate the chemical composition and the antibacterial and modulatory potential of the essential oil of Laurus nobilis and the compound 1, 8-cienol. The essential oil of L. nobilis leaves (OELn) was obtained by hydrodistillation and the chemical components were evaluated by mass spectrometry coupled with mass spectrometry. 1, 8-cineol was obtained commercially. The antibacterial and modulating activity of antibiotics was performed using the microdilution method to determine the minimum inhibitory concentration (MIC). The present study reports In the chemical analysis, 1, 8-cineol was evidenced as the major compound of OELn. It was observed in the antibacterial activity better performance of the tested substances compared to Gram negative bactéria, mainly for Pseudomonas aeruginosa and Escherichia coli . In the modulation tests, the results of the OELn modulatory action were better than the action of 1, 8-cineol, where it can be concluded that the action of the essential oil is mainly performed by the association of its chemical substances. The new information obtained from present study could be helpful in developing OELn as a potential antibacterial agent in near future. Highlights: 1, 8-cineol was identified as the major compound of OELn. The better antibacterial activity of the tested substances was against Gram negative bacteria. In the modulation tests, the results of the OELn modulatory action were better than the action of 1, 8-cineol.